Determinants of School Enrolment in Bhutan: Does Income Matter to Poor? - Nidup, Jigme (Asian Journal of Economic Modelling, 2016)
Household income is a significant determinant in explaining school enrolment in many of the previous studies. However, the implications of income on poor and rich households are less investigated. Therefore, this article examines the determinants of school enrolment for rich and poor households in Bhutan using data from the Bhutan Living Standard Survey, 2012. Findings suggest that income matters so much to the poor as opposed to the rich households. Consequently, Bhutan government should focus on distribution of income from rich to poor in order to maximize school enrolment.